Sedimentation rates from sediment traps and SediMeter sensors in Avillion Admiral Cove Marina, Port Dickson, Malaysia (October 2011–January 2012) - Chin Yik Lin; Su Shiung Lam; Jenn Wei Er; Wah Sza Lee; Ang Jia Hui; Ulf Erlingsson; Yew Sun Gan; Woei Shyan Yee (PANGAEA, 2025)
This dataset includes sedimentation rate measurements obtained using cylindrical Sediment Traps (STs) deployed concurrently with SediMeter (SM) sensors at Avillion Admiral Cove Marina, Port Dickson, Malaysia. Deployments occurred from October 2011 to January 2012. Each ST was installed upright, stabilized with angle bars, and located 2 meters above the seabed. Sediment samples collected in ST bottles were analyzed gravimetrically after filtration and drying. Sedimentation rates (mg cm?^2 day?^1) were computed by dividing the dry weight of collected sediments by the trap area and deployment duration. The average accumulation rate was 16.87 mg cm?^2 day?^1. This dataset was collected to compare sedimentation rates measured directly by STs and indirectly by adjacent SM sensors. The dataset extquotesingles significance lies in addressing discrepancies between traditional sediment trap methods and sensor-based turbidity measurements, providing insights into sediment fluxes and accumulation processes in low-energy marina settings.
In: Lin, CY et al. (2025): Utilizing optical backscatter sensor and sediment traps for measuring sediment dynamics in low energy marine environment [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984064